Usage of DTNs for low-cost IoT application in smart cities: performance evaluation of spray and wait routing protocol and its enhanced versions. (30th April 2021) - Spaho, Evjola
Delay Tolerant Networks (DTNs) can be used as a low-cost solution to implement different applications of Internet of Things (IoT) in a Smart City. An issue that needs to be solved when this approach is used is the efficient data transmission. In this paper, we create a DTN for Smart City, IoT application and enhanced the Binary Spray and Wait (B-S&W) routing protocol to improve delivery probability and average delay. We evaluate and compare the Binary Spray and Wait (B-S&W) routing protocol and our two enhanced versions of Spray and Wait (S&W-V1 and S&W-V2). The simulation results show that the proposed versions S&W-V1 and S&W-V2 improve the delivery probability and average latency.